Description of the use of integrative mixed method in neonatal nursing - Claudia Silveira Viera; Bruna Maria Bugs; Ariana Rodrigues Silva Carvalho; Maria Aparecida Munhoz Gaiva; Beatriz Rosana Gonçalves de Oliveira Toso (SciELO, 2019)
ABSTRACT To describe the application of the integrative mixed method and its steps. Descriptive methodological study. The integrative mixed method approach was exemplified in a study conducted in neonatal nursing on maternal stress throughout the experience of premature newborns' care. Data on maternal stress level (quantitative approach) and maternal perception of care (qualitative approach) were grouped after analyzes made separately according to the analysis technique of each approach. Subsequently, quantitative and qualitative data were integrated, which originated a new set of data to be interpreted, and consequently enabled a greater understanding of the phenomenon under study and emphasized the importance of the integrative mixed method. The integration of the two approaches, qualitative and quantitative, is a denser theoretical framework with strong scientific evidence for a better understanding of the phenomenon under study than the use of a single approach, since, at the same time, it identifies the frequency of the phenomenon and the reason for its occurrence.